2006
DOI: 10.1016/j.ecss.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal distribution and lateral pattern of megalopal settlement and juvenile recruitment of Carcinus maenas (L.) (Brachyura, Portunidae) in the Mira River Estuary, Portugal

Abstract: Settlement is a critical process in the life history of crabs, and thus affecting the abundance, distribution and structure of estuarine communities. The spatial pattern of settlement of megalopae of the shore crab Carcinus maenas along a longitudinal estuarine gradient (Mira River Estuary, Portugal) was examined, as well as its effects on the juvenile population. To measure megalopal settlement, four replicate collectors were deployed in six equally spaced stations along the estuarine axis. Juveniles were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Because cannibalism is quite frequent in C. maenas and size-structured populations develop over that time, very marked density-dependent regulation is expected to be common. First crab instars and sub-adults may coexist in small nursery patches, leading to potential relative prey sizes smaller than 10% (Almeida et al, 2008;Silva et al, 2006), thus favouring cannibalistic interactions. The extent to which these different cohorts can coexist is therefore a crucial variable determining the persistence and stability of shore crab populations.…”
Section: Introductionmentioning
confidence: 99%
“…Because cannibalism is quite frequent in C. maenas and size-structured populations develop over that time, very marked density-dependent regulation is expected to be common. First crab instars and sub-adults may coexist in small nursery patches, leading to potential relative prey sizes smaller than 10% (Almeida et al, 2008;Silva et al, 2006), thus favouring cannibalistic interactions. The extent to which these different cohorts can coexist is therefore a crucial variable determining the persistence and stability of shore crab populations.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2006) found that the settlement rates of Carcinus maenas L. (Brachyura, Portunidae) megalopae were highly variable along the longitudinal axis of an estuary in the Mira River Estuary in Portugal. The lower estuary, however, was less variable and had higher megalopa settlement rate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, estuarine regions can provide refuge for cold-water species at lower latitudes. This has been well-demonstrated along the Iberian Peninsula for a variety of intertidal species, including fucoids (Lorenzen, 2007;Neiva et al, 2012), Carcinus maenas (Silva et al, 2006) and Patella vulgata (FischerPiette, 1955), although the underlying processes are not clear. Enclosed seas (e.g.…”
Section: Drivers Of Changementioning
confidence: 95%